Smart Contract as a Novel Method of Contracting: Many Unanswered Legal Questions - Al Mashhour, Omar Farouk; Abd Aziz, Ahmad Shamsul; Mohd Noor, Nor Azlina (Hasanuddin Law Review, 2025)
Smart contracts have shed light on a new era of contract law, which necessitates a proper legal response to address their unique characteristics, including automation, self-enforcement, coded, immutability, and irreversibility. While these features offer significant legal and practical benefits, they raised critical legal questions. The study aims to identify the legal challenges resulting from the implementation of smart contracts through an in-depth examination of various key aspects. To achieve the intended objective, the study adopted qualitative research utilising the library method and analysing data descriptively and analytically. The study revealed that applying the current conventional contract laws is inadequate and would create a bundle of unprecedented legal questions related to all the life cycle of the contracts, such as legal existence, formation and enforcement, jurisdictional issue, mechanism, unlawful activities, as well as the third parties. The study recommended establishing a specialised framework to address various issues, including the establishment of a regulatory and supervisory body, legislative clarification on various aspects of smart contracts’ such as exchange of will, place, and time, coding language and coding errors, essential functions, jurisdiction and enforcement, ADR, external partners such as Oracle and coding experts, in addition to other matters pertaining to validity and admissibility. Future studies may focus on using these questions as a way to measure the viability of their law to address the emergence of smart contracts.